2003
DOI: 10.1130/g19885.1
|View full text |Cite
|
Sign up to set email alerts
|

Depth of oceanic-crust underplating in a subduction zone: Inferences from fluid-inclusion analyses of crack-seal veins

Abstract: Fluid inclusions in crack-seal veins are analyzed in accreted mélange now on land. The vein I inclusions are observed in the necked parts of sandstone blocks in mélange, and the vein II inclusions developed in shale below the thrust fault, which cuts the mélanges. The pressure and temperature estimations from the inclusions within vein I show that the cracks were sealed at ϳ125-195 ؇C under ϳ92-144 MPa of fluid pressure. Vein II formed in cracks that might have opened in a damage zone caused by the thrust faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 21 publications
4
97
1
1
Order By: Relevance
“…As mentioned above, Matsumura et al (2003) suggested that the site for the initiation of décollement step-down is almost coincident with the location of seismogenesis. This means that the seismogenic fracturing of oceanic basalt near the up-dip limit of the seismogenic zone could nucleate seismic ruptures to propagate along dynamically weakened plate-boundary faults.…”
Section: Implications For Plate-boundary Seismogenesismentioning
confidence: 91%
See 2 more Smart Citations
“…As mentioned above, Matsumura et al (2003) suggested that the site for the initiation of décollement step-down is almost coincident with the location of seismogenesis. This means that the seismogenic fracturing of oceanic basalt near the up-dip limit of the seismogenic zone could nucleate seismic ruptures to propagate along dynamically weakened plate-boundary faults.…”
Section: Implications For Plate-boundary Seismogenesismentioning
confidence: 91%
“…Radiolarian biostratigraphy indicates that the complex is composed of Cretaceous to late Miocene deposits (Taira et al 1988). The maximum paleotemperatures in the complex range from ~150 to 350 °C, as inferred from vitrinite reflectance (e.g., Mori and Taguchi 1988;Laughland and Underwood 1993;Sakaguchi 1996;Ohmori et al 1997;Ohmori 1998;Sakaguchi 1999), illite crystallinity (e.g., Kameda et al 2011b), and fluid inclusion geothermometry (e.g., Matsumura et al 2003).…”
Section: Geological Background and Analyzed Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that the densest methane fluid inclusions methane fluid inclusions fluid inclusions were trapped under nearly lithostatic conditions, because the veins are interpreted to be deposited soon after fracturing under the near-lithostatic fluid pressures Matsumura et al, 2003;Vrolijk, 1987). Densities are assumed to be 2700 kg m m m -3 and 1000 kg m m m -3 , respectively for solid and fluid.…”
Section: Background Geothermal Gradient and Depth At The Initial Stagmentioning
confidence: 99%
“…, Wang and Hu, 1996;Saffer et al, 2003;Bangs et al, 2004;Tobin and Saffer, 2009 , Moore et al, 2001;Kimura et al, 2007;Morgan et al, 2007;Saffer, 2007;Fagereng andSibson, 2010 Kimura andMukai, 1991;Onishi and Kimura, 1995;Hashimoto and Kimura, 1999;Hashimoto et al, 2003;Tokiwa, 2009;Tokiwa andYamamoto, 2011 Matsumura et al, 2003;Shibata and Hashimoto, 2005;Hashimoto et al, 2012 Hashimoto and Kimura, 1999;Hashimoto et al, 2002;Ujiie et al, 2007aIkesawa et al, 2003Kitamura et al, 2005;Ujiie et al, 2007b;Hashimoto et al, 2012Ohmori et al, 1997Sakaguchi, 1999;Kondo et al, 2005;Okamoto et al, 2006;Mukoyoshi et al, 2006;Mukoyoshi et al, 2009 Onishi andKimura, 1995;Kimura, 1999 Shibata andHashimoto et al, 2012Ujiie et al, 2007aIkesawa et al, 2003Kitamura et al, 2005;Mukoyoshi et al, 2006;Okamoto et al, 2006;Ujiie et al, 2007b, Vrolijk et al, 1988…”
mentioning
confidence: 99%